Biphasic Aggregation Responses to ADP and Epinephrine in Some Storage Pool Deficient Platelets: Relationship to the Role of Endogenous ADP in Platelet Aggregation and Secretion - Lages, Bruce; Weiss, Harvey J (Thrombosis and Haemostasis, 1980)
Biphasic aggregation responses to ADP and epinephrine have been consistently observed in platelets of two patients with storage pool deficiency (SPD) despite marked reductions in platelet ADP contents. The nature of these aggregation responses was examined in relation to the role of secreted ADP as a mediator of secondary aggregation. Platelets from these patients secreted greater quantities of ADP after stimulation by epinephrine than did SPD platelets with comparable ADP deficiencies and absent second-phase aggregation, and were more sensitive than both other SPD platelets and normal platelets to the aggregating effects of low concentrations of ADP. Epinephrine-induced secondary aggregation was also associated with measurable, though less than normal, MDA formation in these patients' platelets, whereas no MDA formation occurred in SPD platelets with impaired epinephrine responses. CP/CPK did not inhibit epinephrine-induced responses in the SPD patients showing biphasic aggregation, whereas these responses in normal platelets were inhibited only with higher levels of CP/CPK than those required for inhibition of the responses to exogenous ADP. These findings suggest that secondary aggregation responses may be mediated by both prostaglandin endoperoxide production and secreted ADP, and are consistent with the possibility that such mediation is primarily an intracellular process.
Keywords: Biphasic aggregation; Storage pool deficiency; Platelet ADP